Advanced fitness assessment and exercise prescription - Gibson, Ann L. 1953- PhD; Heyward, Vivian H. PhD; Wagner, Dale R. 1966- PhD (Human Kinetics, 2019)
Advanced Fitness assessment and Exercise Prescription, eight edition, provides a comprehensive approach to physical fitness appraisal and customized exercise prescription. The text synthesizes research and practice with concepts and theories from exercise physiology, kinesiology, measurement, psychology, and nutrition to clearly convey how assessments from physical fitness testing inform the design of individualized exercise programs. This eighth edition reflects the latest exercise testing and prescription guidelines from the American College of Sports Medicine (ACSM) as well as physical activity recommendations from the U.S. government and American Heart Association. Additional updates include the following: significant expansion of the online video clips, which now demonstrate nearly 75 fitness tests; new protocols and assessments for each of the five fitness components; updated blood pressure standards for hypertension; expanded information on the use of workspace design to promote physical activity; extensive updates to the supporting research for the assessment and testing protocols. Structured around five physical fitness components-cardiorespiratory endurance, muscular fitness, body composition, flexibility, and balance-the text offers both field and laboratory assessment and testing protocols, followed by prescription guideline to improve each fitness component. It truly bridges the gap between research and practice with its unique scope and depth of coverage in assessing fitness and designing individualized exercise programs